The influence of service quality, passenger satisfaction, perceived value, and airline brand love on word-of-mouth behavior among domestic airline users in Indonesia - Mariani; Fauzan Qamaar; Anita Dyah Nur'aini (Priviet Social Sciences Journal, 2024)
This study aims to analyze the impact of crucial dimensions in the Indonesian domestic airline industry, namely Service Quality, Passenger Satisfaction, Perceived Value, and Airline Brand Love, on Word of Mouth (WOM) behavior among passengers. Data was collected from respondents who are users of domestic airlines in Indonesia. The analysis revealed several key findings. Firstly, Passenger Satisfaction has a significant positive influence on both Airline Brand Love and Word of Mouth. This relationship is supported by the calculated t-value exceeding the critical t-value and the significance level (P-value) being less than 0.05. Therefore, to increase sales, improving passenger satisfaction levels should be a priority. Secondly, Perceived Value does not have a significant positive influence on either Airline Brand Love or Word of Mouth. This is evident from the calculated t-value being lower than the critical t-value and the P-value being greater than 0.05. Nevertheless, it's important to still consider the aspect of Perceived Value in efforts to enhance customer experience. Thirdly, Service Quality has a proven significant positive influence on Airline Brand Love, but not on Word of Mouth. This positive relationship is indicated by the calculated t-value exceeding the critical t-value and the significance level being less than 0.05. In this context, improving service quality can be a crucial factor in building brand love for the airline. Thus, this study provides insights into the factors influencing Word of Mouth behavior in the Indonesian domestic airline industry. The implications of these findings are the need for airline companies to focus on improving passenger satisfaction and service quality to strengthen the connection between Passenger Satisfaction, Airline Brand Love, and Word of Mouth. Additionally, although Perceived Value does not have a significant impact in this context, it remains important to consider this factor in efforts to maintain customer satisfaction and loyalty.